Hidden : betrayed, exploited and forgotten : how one boy overcame the odds - Glass, Cathy; Cathy Glass, Clays Ltd, St Ives plc (London : HarperElement, 2008)
From the author of 'Damaged' comes the poignant and shocking memoir of Cathy's recent relationship with Tayo, a young boy she fosters whose good behaviour and polite manners hide a terrible past.
Originally published: 2007.
Not included
Adult